Identifikasi Dampak Penggunaan Sistem Informasi Rumah Sakit (SIRS) Terhadap Pelayanan Kesehatan Menggunakan Hot-Fit Model 2006 - Frendy Rocky Rumambi; Salahudin Robo; Citra Amalia (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Hospital Information System (SIRS) is an integrated information system that aims to handle all hospital management processes, ranging from diagnostic services, medical data measures, medical records, pharmaceuticals, pharmaceutical warehouses, billing, personnel databases, payroll, and accounting to the control management. Based on Indonesian Constitution No. 44 Article 52 year 2009, paragraph 1 states that "Indonesian hospitals are required to record and report all activities that occur within a hospital". On the Indonesia ministry regulation, PERMENKES No. 1171 year of 2011, Article 1 paragraph 1 states that "Each hospital is required to apply SIRS". Therefore Dr. Samratulangi Tondano District Hospital of Minahasa Regency in the North Sulawesi uses SIRS to improve employee performance in providing health services to the community. The paper discussed how to identify the impact of the use of Hospital Information Systems (SIRS) on health services. The purpose of this study is to look at the impact of the use of the SIRS system based on four indicators contained in the 2006 Human Organizational Technology (HOT-Fit) method in addition to the DeLone and McLean Success 2003 methods. By taking 150 respondents of SIRS users randomly, data were collected and analyzed using SPSS and AMOS software.The four hypotheses derived from three components namely "Technology", "Human" and "Organization" have a positive impact and provide a net benefit to the use of the system. In short, the majority of users SIRS only focuses on functions for registration and administration rather than clinical functions. The availability of IT units and IT personnel influences the use of SIRS as well.